Ginger (Zingiber officinale) powder improves growth performance and immune response but shows limited antioxidant capacity for Nile tilapia infected with Aeromonas hydrophila - Naliato, Rafael Fogaça [UNESP]; Carvalho, Pedro Luiz Pucci Figueiredo [UNESP]; Vicente, Igor Simões Tiagua [UNESP]; Xavier, William dos Santos [UNESP]; Guimarães, Matheus Gardim [UNESP]; Rodrigues, Edgar Junio Damasceno [UNESP]; Ito, Paulo Incane [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Orsi, Ricardo de Oliveira [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP] (Wiley, 2021)
Fish were fed diets containing dehydrated ginger powder (GgP) to determine its effects on growth, immune response, antioxidant capacity and resistance to Aeromonas hydrophila infection. 540 Nile tilapia were distributed in 36 250 L aquaria and fed six isonitrogenous and isoenergic diets supplemented with six graded levels of GpP: 0, 2.5, 5, 7.5, 10 and 15 g/kg, during 30 days. After that, growth, hemato-immunological parameters and antioxidant enzymes activities were determined. All parameters, but growth, were re-evaluated after the bacterial infection challenge. Fish fed diets up to 5 GgP showed higher body weight and specific growth rate compared with 0 GgP. Fish fed 10 GgP showed the highest H2O2 and NO compared with 0 GgP (p <.05). Fish fed 2.5 GgP and 10 GgP maintained catalase and superoxide dismutase activities after infection. The highest survival was observed for fish fed 10 GgP. The best results for specific growth rate and feed conversion ratio were determined at 4.1 and 5.8 g/kg of GgP and for survival rate and immunological response at 10 g/kg of GgP. In sum, 10 g/kg GgP is indicated to improve Nile tilapia growth performance and resistance against Aeromonas hydrophila infection.
Keywords: bacterial challenge; immunostimulant; Oreochromis niloticus; oxidative stress; phytogenic compounds; zingiberene